Enhancing Learning Outcomes: The Impact of Competition on Slow Learners’ Engagement and Academic Performance - Magdum, Rohit; Jadhav, Prashant; Magdum, Anjali; Shirguppikar, Shailesh; Deasavale, Ramchandra; Khot, Sachin (Journal of Engineering Education Transformations, 2025)
The classroom management plays a crucial role in enhancing students’ understanding and engagement. This study introduces "Learning by Competing," a novel approach aimed at involving slow learners—students with below-average cognitive abilities who often remain passive during classroom activities. The method was implemented in a classroom of 30 students enrolled in a Textile Technology elective course, known for its challenging and theoretical content. The approach involves dividing the class into heterogeneous groups, with slow learners assigned as group leaders. These leaders, along with their groups, actively participate in a structured competition, which involves data collection, discussion, and presentation. The competitive environment fosters engagement, listening, and responsibility among all students, particularly motivating slow learners to take on leadership roles. Results demonstrate that this method significantly improved students’ understanding, with a 30% increase in average marks between two-unit tests and ESE by 15 %. This approach effectively transforms slow learners into active participants, thereby enhancing the overall learning experience.